Ground thermal conditions at Chachani Volcano, Southern Peru - De Andrés de Pablo, Nuria; Palacios Estremera, David; Úbeda Palenque, José; Alcalá Reygosa, Jesús (Geografiska Annaler: Series A, Physical Geography, 2011)
Shallow ground temperatures were measured and periglacial and permafrost environments identified at the Chachani volcanic complex in the west-central Andes in southern Peru (16° 11′ S; 71° 31′ W, elevation 6057 m a.s.l.). Three stations were installed at 4850, 4976 and 5331 m a.s.l. on the southern slope and the data were processed to produce ground temperature distribution models at depth and altitude. Snow cover lasts only a few days each year. Air and ground surface temperatures oscillate around 0°C almost daily, but the temperature is stabilized only a few centimetres below the ground surface. The lower limit of thermal conditions for isolated patches of permafrost occurs at 5050 m on the south-facing slopes. Thermal conditions associated with discontinuous permafrost occur from 5250 to 5420 m a.s.l., with continuous permafrost found above this level. The permafrost distribution models show that the rock glaciers observed on the southern slopes of the complex are within the active permafrost zone. Ministerio de Ciencia e Innovación (España) Depto. de Geografía Fac. de Geografía e Historia TRUE pub